PENGEMBANGAN MEDIA BUKU MELODI PADA MATERI CERPEN SISWA SMALB - Arumdapta, Rananda; Devi, Wika Soviana (Universitas Peradaban, 2025)
This study aims to develop audiobook media on short story material for students of Special Needs High Schools (SMALB) and to test its feasibility and practicality in learning Indonesian. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The product developed is a melody book (audiobook) on short story material that contains the definition of short stories, characteristics of short stories, types of short stories, intrinsic and extrinsic elements of short stories, as well as examples of short stories integrated with Pancasila values. The research subjects included material experts, media experts, and SMALB students as users. Data collection techniques used expert validation sheets and student response questionnaires. The results of the study showed that the melody book media was in the very feasible category based on the assessment of material experts and media experts. In addition, the trial results showed that the melody book media was practical to use and helped SMALB students in understanding short story material more optimally through audio media. Thus, the developed melody book media can be used as an alternative Indonesian language learning media for SMALB students.